Production of cashew CP076 seedlings using different types of substrates (Research, Society and Development, 2022)
Cashew farming has great national expression and in recent years, it has been introduced in the State of Tocantins, mainly due to climate adaptation. In this sense, we seek to obtain new technologies to achieve greater productivity. The objective was to evaluate different substrates in the formation of cashew seedlings in the climatic conditions of the State of Tocantins. The experiment was carried out in the Experimental Sector of Agronomy of UNITPAC, from August 1, 2019 to June 30, 2020. Fourteen types of substrates were used in the production of cashew seedlings CCP76, composed of ravine soil (SB) , residue from fish farming (PS), Sand (AR), Vermicultia (VE) and Tropstrato (TR) ponds. The response variables analyzed were: stem diameter (mm) and plant height (cm). To determine the height of the shoot, a ruler graduated in millimeters was used, measuring the distance between the stem and the apex of the seedling. The stem diameter was measured at 1 cm from the ground, using a digital caliper with the reading given in millimeters. Data were submitted to analysis of variance and means were evaluated by boxplot using Sisvar software. The experimental design was in randomized blocks with 14 treatments, 5 replications. Thus, the substrate composed of 75% of Tropstrate and 25% of sand presents better development of the height and diameter of the plants.